The long-term care system in Denmark - Erika Schulz (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This document provides an overview of the long-term care system, the number and develop-ment of beneficiaries and the long-term care policy in Denmark. The report is part of the first stage of the European project ANCIEN (Assessing Needs of Care in European Nations), commissioned by the European Commission under the Seventh Framework Programme (FP7). The first part of the project aims to facilitate structured comparison of the long-term care systems and policies in European Nations. Thus, this report is one of comparable reports provided for most European countries.
info:eu-repo/grantAgreement/EC/FP7/223483
Keywords: H51; I18; I19; 330; Long-term care system; long-term care policy; beneficiaries; Pflegedienst; Dänemark